Optimizing Green Energy Consumption of Fog Computing Architectures - Gougeon, Adrien; Camus, Benjamin; Orgerie, Anne-Cécile (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2020)
The Cloud already represents an important part of the global energy consumption, and this consumption keeps increasing. Many solutions have been investigated to increase its energy efficiency and to reduce its environmental impact. However, with the introduction of new requirements, notably in terms of latency, an architecture complementary to the Cloud is emerging: the Fog. The Fog computing paradigm represents a distributed architecture closer to the end-user. Its necessity and feasibility keep being demonstrated in recent works. However, its impact on energy consumption is often neglected and the integration of renewable energy has not been considered yet. The goal of this work is to exhibit an energy-efficient Fog architecture considering the integration of renewable energy. We explore three resource allocation algorithms and three consolidation policies. Our simulation results, based on real traces, show that the intrinsic low computing capability of the nodes in a Fog context makes it harder to exploit renewable energy. In addition, the share of the consumption from the communication network between the computing resources increases in this context, and the communication devices are even harder to power through renewable sources.